Midbrain hyperechogenicity, hyposmia, mild parkinsonian signs and risk for incident Parkinson's disease over 10 years: A prospective population-based study. (January 2020) - Mahlknecht, Philipp; Stockner, Heike; Marini, Kathrin; Gasperi, Arno; Djamshidian, Atbin; Willeit, Peter; Kiechl, Stefan; Willeit, Johann; Rungger, Gregorio; Poewe, Werner; Seppi, Klaus
Abstract: Introduction: Associations of substantia nigra (SN) hyperechogenicity on transcranial sonography, olfactory dysfunction, and mild parkinsonian signs (MPS) with incident Parkinson's disease (PD) have only been studied over limited periods of follow-up and their long-term predictive properties are unclear. We aimed to prospectively assess the risk for incident PD over 10 years in community-dwelling elderly individuals with these risk markers. Methods: SN-hyperechogenicity, olfactory function, and MPS were assessed in the prospective population-based Bruneck Study (2005 in-person assessment; n = 574, aged 55–94 years). Cases of incident PD were identified at 5-year and 10-year follow-up visits. We estimated relative risks of baseline markers for incident cases. Results: After excluding 35 cases with PD or secondary parkinsonism at baseline, a total of 20 cases of incident PD were identified from the remaining 539 participants (11 at 5 years and 9 at 10 years). Relative risks for incident PD over the 10-year follow-up period were 7.43 (2.71–20.39), 3.60 (1.48–8.78), and 5.52 (2.43–12.57) for baseline SN-hyperechogenicity, hyposmia, and mild parkinsonian signs, respectively. While risk of hyposmia for incident PD was similar for the two sequential 5-year periods studied, relative risks of SN-hyperechogenicity and MPS were higher for the first five years as compared to later. Conclusion: Our findings extend the established risk relationship of SN-hyperechogenicity, hyposmia, and MPS with incident PD beyond 5 years of follow-up. Highlights: We assessed substantia nigra hyperechogenicity, hyposmia, and mild parkinsonian signs as long term risk markers for Parkinson's disease. All three markers were associated to a significantly increased risk over 10 years. Hyposmia was the only marker with similar risk short- and long term risk (<5 and 5–10 years). The risk related to substantia nigra hyperechogenicity and mild parkinsonian signs was higher for the first 5 years.